Adaptation and Validation of General Self-Efficacy Scale for Higher Education - Fadila Dian Wardani; Damajanti Kusuma Dewi; Miftakhul Jannah; Riza Noviana Khoirunnisa; Hanandita Veda Saphira (IJORER : International Journal of Recent Educational Research, 2025)
Objective: Self-efficacy is a psychological factor that plays a crucial role in students' academic success. However, its measurement instruments need to be adapted to the cultural characteristics and local population. This study aims to adapt and validate the General Self-Efficacy Scale (GSES) within the context of higher education in Indonesia. Method: This study involved 748 third-semester students from various faculties at the State University of Surabaya. The adaptation process followed the five stages proposed by Beaton et al. (2000), which include translation, synthesis, back translation, expert committee review, and pretesting. The validation test was conducted using Confirmatory Factor Analysis (CFA). Results: After a successful adaptation process, the scale demonstrated high reliability, ranging from 0.760 to 0.801. The CFA results showed a Kaiser-Meyer-Olkin (KMO) score of 0.949, indicating that the data met the requirements for factor analysis. Strong factor loadings (0.752–0.810) were observed for each item, confirming their alignment with the self-efficacy construct. Cross-cultural comparisons with countries such as Germany, Spain, and China further affirmed the validity of the GSES in the Indonesian context, despite minor differences in certain items. Novelty: The cultural adaptation of the GSES for higher education in Indonesia provides a valid and reliable measurement tool, making this study a novel contribution to the field.